Respostas

2013-11-28T08:24:12-02:00
X² +( x +1 )² + ( x + 2 ) ² = 50   resolvendo o produtos notáveis
x² + x² + 2x + 1 + x² + 4x + 4 = 50 
3x² + 6x + 5 - 45 = 0
3x² + 6x - 45=0   

delta = 6² - 4 . 3 . -45 = 36 + 540 = 576 

x =( - 6 + 24 ) / 6 = 3   e     x' = (-6 - 24 ) / 6 = - 5 

x = 3
temos 
x² = 3 ² = 9
(x + 1)² = ( 3 + 1 )² = 4² = 16
( x+2)² = ( 3 +2)² = 5² = 25  

logo 9+ 16 + 25 = 50 
2013-11-28T09:32:28-02:00
(x-1)² + x² + (x+1)² = 50
x²-2x+1+x²+x²-2x+1 = 50
3x²+2 = 50
3x² = 50-2
3x² = 48
x² = 48/3
x² = 16
x = \/16
x = 4
(x-1) = (4-1) = 3
(x+1) = (4+1) = 5

Os números são 3, 4 e 5
1 5 1